Stillborn child with diffuse SARS-CoV-2 viral infection of multiple organs - Vsevolod A. Zinserling (Elsevier, 2021)
In May 2020, a pregnant woman in her 37th pregnancy week was diagnosed with COVID-19 in St. Petersburg in Russia. All treatments failed and the patient died after 11 days due to acute respiratory distress syndrome. A stillborn child was removed by caesarian section. Pathological investigations showed that the child died due to antenatal asphyxia with aspiration pneumonia. The child was positive for SARS-CoV-2 and immunohistochemical investigations showed viral infection and cellular changes in several organs such as pancreas, brain, spleen, and adrenals. These results emphasize the importance of vaccinating pregnant women against SARS-CoV-2.